Pelatihan Membuat Stik Lele dan Pentol Lele sebagai Inovasi Produk Jajanan Rakyat - Ariefah Yulandari; Nang Among Budiadi; Sugiyarmasto Sugiyarmasto; Sugiarti Sugiarti; Widi Hariyanti (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
The Micro, Small, and Medium Enterprises (MSMEs) in Kismoyoso Village, Boyolali, widely known for their traditional herbal medicine, aimed to diversify their product offerings to foster long-term development. This initiative focuses on creating sustainable product concepts designed to establish a robust local supply chain and build partnerships among residents, thereby increasing community consumption expenditure and stimulating the village's internal economic turnover. Catfish was selected as the core ingredient due to its high nutritional value and versatility in various food products and snacks. Consequently, the MSME members—primarily local women—embraced the idea of developing catfish sticks and catfish meatballs as their new flagship products. To facilitate this, a community service team from the Faculty of Business, Setia Budi University, conducted a comprehensive training program. The training utilized five distinct methods: direct explanation, demonstration, hands-on practice, discussion/Q&A sessions, and product evaluation. Through active participation in each stage, the trainees successfully produced catfish sticks and meatballs, establishing them as viable processed snack products ready to drive the future growth of MSMEs in Kismoyoso Village, Boyolali.